Immunotherapy Strategy for Systemic Autoimmune Diseases: Betting on CAR-T Cells and Antibodies - Vitaly Chasov; Ekaterina Zmievskaya; Irina Ganeeva; Elvina Gilyazova; Damir Davletshin; Marat Khaliulin; Emmanuel Kabwe; Yuriy N. Davidyuk; Aygul Valiullina; Albert Rizvanov; Emil Bulatov (Antibodies, 2024)
Systemic autoimmune diseases (SAIDs), such as systemic lupus erythematosus (SLE), systemic sclerosis (SSc) and rheumatoid arthritis (RA), are fully related to the unregulated innate and adaptive immune systems involved in their pathogenesis. They have similar pathogenic characteristics, including the interferon signature, loss of tolerance to self-nuclear antigens, and enhanced tissue damage like necrosis and fibrosis. Glucocorticoids and immunosuppressants, which have limited specificity and are prone to tolerance, are used as the first-line therapy. A plethora of novel immunotherapies have been developed, including monoclonal and bispecific antibodies, and other biological agents to target cellular and soluble factors involved in disease pathogenesis, such as B cells, co-stimulatory molecules, cytokines or their receptors, and signaling molecules. Many of these have shown encouraging results in clinical trials. CAR-T cell therapy is considered the most promising technique for curing autoimmune diseases, with recent successes in the treatment of SLE and SSc. Here, we overview novel therapeutic approaches based on CAR-T cells and antibodies for targeting systemic autoimmune diseases.